A discourse analysis of cultural humility within counseling dyads. (19th October 2022) - Zhu, Peitao; Isawi, Dana T.; Luke, Melissa M.
Abstract: A growing body of empirical literature has substantiated that cultural humility (CH) contributes meaningfully to a variety of therapeutic processes and outcomes. However, no study has concretely described how CH is linguistically and discursively enacted within therapeutic exchanges. Using interactional sociolinguistic discourse analysis, we explored the sociolinguistic strategies along with three dimensions of CH: (a) cultural teachability, (b) lack of cultural arrogance, and (c) relational orientation. Participants included six pairs of cross‐racial counseling dyads. Our analyses of the session and follow‐up interview transcripts yielded a range of sociolinguistic strategies (i.e., positioning, use of reinforcement, repetition, and use of pronouns) corresponding to the CH dimensions. We discuss clinical, research, and training implications.